Letter from James Curtis Booth to Mr. F. Sylvester - Booth, James Curtis (1880)
James Curtis Booth (1810-1888) writes to Mr. F. Sylvester concerning papers needed for sale of property.
Keywords: Booth, James Curtis, 1810-1888; Real property; Sylvester, F.